Theorizing Mental Health Courts - E. Lea Johnston (Washington University Law Review, 2012)
To date, no scholarly article has analyzed the theoretical basis of mental health courts, which currently exist in forty-three states. This Article examines the two utilitarian justifications proposed by mental health court advocates—therapeutic jurisprudence and therapeutic rehabilitation—and finds both insufficient. Therapeutic jurisprudence is inadequate to justify mental health courts because of its inability, by definition, to resolve significant normative conflict. In essence, mental health courts express values fundamentally at odds with those underlying the traditional criminal justice system. Furthermore, the sufficiency of rehabilitation, as this concept appears to be defined by mental health court advocates, depends on the validity of an assumed link between mental illness and crime. In particular, mental health courts view participants’ criminal behavior as symptomatic of their mental illnesses and insist that untreated mental illness serves as a major driver of recidivism. Drawing upon social science research and an independent analysis of mental health courts’ eligibility criteria, this Article demonstrates that these relationships may not hold for a substantial proportion of individuals served by mental health courts. The Article concludes by identifying alternative theories that may justify this novel diversion intervention.
Keywords: Mental health courts; Recidivism; Therapeutic jurisprudence; States; United States